Analisis Pengaruh Brand Awareness, Brand Image, dan Brand Trust terhadap Brand Loyalty nasabah tabungan BritAma di Jakarta Pusat - Damarresa Adi Bharata; Zoel Hutabarat (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to examine the influence of Brand Awareness, Brand Image, and Brand Trust on Brand Loyalty. Research data was obtained through a survey involving 212 respondents. This research uses primary data obtained from questionnaires distributed online and directly in the Central Jakarta area via Google Form. The sampling technique was non-probability sampling, with the main respondents being BritAma Savings customers. This research uses a quantitative approach by applying the Partial Least Square Structural Equation Modeling (PLS-SEM) method. This research is expected to provide knowledge to BRI management to further increase Brand Loyalty through increasing Brand Awareness, Brand Image and Brand Trust. The research results explain that there is a positive and significant influence between Brand Awareness, Brand Images, Brand Trust and Brand Loyalty.